2013
DOI: 10.7860/jcdr/2013/6291.3755
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Spectrum of Endometrial Changes in Peri-menopausal and Post-menopausal Abnormal Uterine Bleeding: A 2 Years Study

Abstract: Background: Abnormal uterine bleeding is the Common pre senting complaint in Gynaecology Outpatient Department in all age groups. It is due to the anovulatory cycles which are commonly seen in adolescent and perimenopausal women. Abnormal uterine bleeding is caused by wide variety of organic or nonorganic causes. Histopathological examination of endometrial sample remains the gold standard for diagnosis of endometrial pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
30
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 8 publications
8
30
1
Order By: Relevance
“…11 However, most other studies have observed a higher incidence with 29.16%, 35.09%, and 38.5% of cases. 9,13,14 Secretory phase of endometrium was seen in 16.11% cases, which is in concordance with the result of the study by Patil et al 15 Atrophic endometrium comprised of 14 (7.78%) cases of AUB and was the most common in postmenopausal women. In other studies its incidence varies from 1.1%-7%.…”
Section: Discussionsupporting
confidence: 81%
“…11 However, most other studies have observed a higher incidence with 29.16%, 35.09%, and 38.5% of cases. 9,13,14 Secretory phase of endometrium was seen in 16.11% cases, which is in concordance with the result of the study by Patil et al 15 Atrophic endometrium comprised of 14 (7.78%) cases of AUB and was the most common in postmenopausal women. In other studies its incidence varies from 1.1%-7%.…”
Section: Discussionsupporting
confidence: 81%
“…Most of the patients showing this pattern were in perimenopausal age group in the present study similar to the observations made by Damle RP. 7 Bleeding in secretory phase is due to ovulatory dysfunction. Disordered proliferative pattern is characterized by foci of dilated irregularly shaped glands with focal outpouchings and branching as seen in 20 (8%) cases in present study.…”
Section: Discussionmentioning
confidence: 99%
“…17 But, lowest incidence was reported by Damle RP (7.95%) and Selvi A et al (10.77%). 6,18 Disordered proliferative pattern of the endometrium is somewhat difficult to define; it refers to a proliferative phase endometrium due to persistent oestrogen stimulation. It occupies the lower end of spectrum which passes through the hyperplasia to endometrial carcinoma on the other end.…”
Section: Resultsmentioning
confidence: 99%
“…Eventually, surgical management was given to 94 patients (Table 6). [4][5][6][7] In perimenopausal women abnormal uterine bleeding may display in different menstrual patterns, these are heavy menstrual bleeding, frequent menstrual cycles, inter-menstrual bleeding, dysmenorrhoea and amenorrhea followed by continuous heavy bleeding.…”
Section: Resultsmentioning
confidence: 99%